ENGLISH LANGUAGE LEARNER’S WRITING COMPETENCE INSMP NEGERI 2 EMPANG - Martina Laela; Muhamad Suhaili (Sinar Lima, 2025)
Many students face challenges in mastering English vocabulary, impacting their writing competence. The most common challenges are lack of vocabulary knowledge, inappropriate word usage, and difficulty in constructing coherent sentences. This study aims to describe the English writing competence of grade IX students at SMP Negeri 2 Empang. Using a qualitative research method with a qualitative descriptive approach, this study provides an in-depth analysis of students' writing ability. The research subjects consisted of ninth-grade students in the 2024/2025 academic year who were selected as data sources. Based on the results from the documentation data and assessment categories, it shows that students' writing competence varies significantly based on their academic ability level, with students who have high competence showing better ability in organizing ideas, cohesion, and the use of relevant vocabulary. In contrast, students with low competence continue to face challenges in mechanical aspects such as grammar, punctuation, and spelling. To improve students' writing competence, it is crucial to implement a process-based approach that includes writing stages such as prewriting, writing, revising, and editing, as well as constructive feedback between teachers and students.